Penanda Kohesi Gramatikal dan Kohesi Leksikal pada Novel Pramoedya Karya Tenderlova dan Implikasinya terhadap Pembelajaran Bahasa Indonesia di SMP - Yessi Vita Kusumaningrum; Petrus Poerwadi; Indra perdana; Albertus Purwaka (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2025)
The aims of this research are (1) to describe the forms of grammatical cohesion in Pramoedya novel by Tenderlova, (2) to describe the forms of lexical cohesion in Pramoedya novel by Tenderlova, and (3) to describe the implications of the results of this research for writing learning in junior high schools. The research method used in this study is a qualitative method. Qualitative research methods are used to describe the forms of grammatical cohesion and lexical cohesion in Pramoedya novel by Tenderlova and to describe the implications of grammatical cohesion and lexical cohesion in Pramoedya novel by Tenderlova on Indonesian language learning in junior high schools.The results of the study show that: (1) In Pramoedya novel by Tenderlova there is grammatical cohesion in the form of 27 data references, 2 data substitutions, 14 data ellipsis, and 29 data conjunctions. References and conjunctions are the most dominant forms, especially pronouns such as he, I, they, she, and the clitic -nya, then additive conjunctions such as and, or, also, then adversative conjunctions namely but and whereas, causal conjunctions namely because, so, and then, and temporal conjunctions such as later, since, finally, before, after that, then, and when. (2) In addition, lexical cohesion was also found in the form of 5 data general nouns, 10 data repetitions, and 4 data collocations, with the repetition of the same word as the dominant form that functions to strengthen the description, atmosphere, and identity of the characters and conflicts. (3) These findings can be used in writing lessons in junior high schools as teaching materials that include definitions, examples and analysis, in order to improve students' reading competence and writing skills so that the texts produced are coherent and sequential.